1991
DOI: 10.1007/bf00029305
|View full text |Cite
|
Sign up to set email alerts
|

Container seedlings outperform barefoot stock: Survival and growth after 10 years

Abstract: Application . Survival and growth of ponderosa pine (Pinus ponderosa Dougl . ex Laws . var. ponderosa), Jeffrey pine (P. Jeffreyi Grev . & Balf .), and Douglas-fir (Pseudotsuga menziesii [Mirb .] Franco) seedlings were almost always higher if grown in containers and planted as plugs than planted as bareroot stock . If costs were similar, forest managers could consider using container stock on sites similar to those in this California study .Abstract . Ponderosa pine, Jeffrey pine, and Douglas-fir seedlings wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 6 publications
0
10
0
1
Order By: Relevance
“…Johansson et al 2007;McDonald 1991). General trends have been identified, notably regarding the positive relationship between seedling initial dimensions and growth (Newton et al 1993;Jobidon et al 2003).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Johansson et al 2007;McDonald 1991). General trends have been identified, notably regarding the positive relationship between seedling initial dimensions and growth (Newton et al 1993;Jobidon et al 2003).…”
Section: Introductionmentioning
confidence: 94%
“…in the presence of shallow-rooted herbaceous species versus deep-rooted woody plants (Balandier et al 2006). Based on 10 year results, McDonald (1991) concluded that containerized seedlings of Pinus ponderosa, P. jeffreyi Grev. & Balf.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, large seedlings can be produced either in containers or as bareroot stock. Field comparisons of containerized and bareroot seedlings are numerous (e.g., [19][20][21][22]). However, most studies have examined stock types of different initial dimensions (see [23]); few have investigated the relative performance of bareroot and containerized seedlings that are similar in size at the time of planting [24][25][26].…”
Section: International Journal Of Forestry Researchmentioning
confidence: 99%
“…can be planted on a variety of reforestation sites without experiencing lethal water stress. Planting bare-root or containerized spruce stock types could play a significant role in the success of plantation establishment [33]. These stock types generally differ in their water relations during the first few years after planting; bare-root seedlings generally experience greater planting stress than containerized seedlings [1,40].…”
Section: Introductionmentioning
confidence: 99%